Pumping Life Into Your Classroom: Using CPR Training to Teach Principles of Training Design. (September 2019) - Bear, Stephen E.; Behson, Scott
We present an experiential exercise to teach key principles of training design. Selected students participate in a self-learning cardiopulmonary resuscitation training program, CPR Anytime®, offered by the American Heart Association, while the rest of the class observes. The class then assesses the use of several training design principles in the observed program. Finally, students discuss the strengths and weaknesses of the training program, making recommendations for improvement.